Estudo das alterações neurológicas centrais e periféricas em pacientes com doença de Wilson em um hospital universitário do estado do Ceará - Sobrinho, Jéssica Queiroz de Sousa (2021)
Wilson's disease (DW) is a rare autosomal recessive disorder, not linked to sex, due to a mutation in the ATP7B gene, which generates changes in copper metabolism. It is a systemic disease characterized by hepatic, neurological and musculoskeletal disorders. Studies carried out with people affected by this disease in Brazil involved only the population of the south and southeast of the country. The aim of this study was to describe the central and peripheral neurological disorders in patients with Wilson's disease in the state of Ceará. 14 patients with a conclusive diagnosis of DW were recruited, accompanied by a neurologist at the Hospital Universitário Walter Cantídio (HUWC). Patients had their medical records reviewed; performed anamnesis, neurological evaluation, skin wrinkle test and answered the Quality of Life Determination (DEFU) questionnaires, Barthel Index and the Compound Score of Autonomic Symptoms (COMPASS 31). The mean age at the time of the patient survey was 39.4+ 2.61 years (25 to 53 years). All patients had neurological changes. Among these 8 had a positive family history of DW involving siblings, cousins and nephews, 10 patients had consanguineous parents and 6 lived in inland regions. The average age for the conclusive diagnosis of DW was 24.5 years ± 1.40 years (from 13 to 34 years). The most common neurological symptoms were: tremor, dysphagia, dysarthria, change in gait, stiffness, drooling, speech disorders and bradykinesia. The most common neurological signs were: tremor, cogwheel signal, Kayser Fleisher rings and Babinski signal. The most widely used pharmacological treatment was penicillamine. The most reported psychiatric symptom was depression. Among the evaluated patients, 71.4% (10) presented some symptom of autonomic dysfunction, of which 57% (8) obtained an abnormal result in the skin wrinkle test by immersing the hand in water. Among the neurological characteristics presented by the patients in this study, the involvement of sensitive and autonomic peripheral nerve fibers from the skin wrinkle test stands out. Our study proves the presence of peripheral neuropathy in 50% of patients affected with DW, as well as the correlation of this dysfunction with the presence of autonomic disorders.